Use of the Columbia-Suicide Severity Rating Scale (C-SSRS) to Classify Suicidal Behaviors. Issue 2 (3rd April 2018) - Interian, Alejandro; Chesin, Megan; Kline, Anna; Miller, Rachael; St. Hill, Lauren; Latorre, Miriam; Shcherbakov, Anton; King, Arlene; Stanley, Barbara
Abstract : Efforts to better understand and prevent suicide have increasingly pointed to the prospective assessment of suicidal behaviors in clinical trials. These assessments are aided by instruments such as the Columbia-Suicide Severity Rating Scale (C-SSRS), which have sought to improve the conceptual uniformity and ease by which suicidal behaviors are classified. At the same time, assessment and classification of suicidal behaviors has been a longtime challenge in the field. To aid users of the C-SSRS, this article illustrates the use of the C-SSRS in instances where classification complexities arise. Illustrations are presented based on cases encountered during a clinical trial for a suicide prevention intervention. Key decision points are summarized and classification issues that warrant consideration for future refinement of such decisions are discussed.